DO THE INDEPENDENT COMMISSIONERS CONCERN OF TIMELINESS OF FINANCIAL REPORT PUBLICATION ON THE INDONESIA STOCK EXCHANGE (BEI) - Berna Ratna Sari; Muhammad Hasymi; Nurul Inayati Irianti (Management Research Studies Journal, 2020)
Accuracy and timely publication are important so that the benefits of Financial Statements for corporate stakeholders in decision making are achieved. For this reason, this study aims to examine the factors that affect the timeliness of the publication of public company financial statements on the Indonesia Stock Exchange. This research was conducted using 186 company samples for 3 years (2016 - 2018) with a logistic regression test. The results showed that the audit tenure (the length of a partnership that exists between public clients / companies and the Public Accounting Firm) has a significant effect on the timeliness of the publication of financial statements, while the existence of an Independent Commissioner, the size of assets and capital structure of public companies have no significant effect. This shows that the relationship between the Public Accounting Firm and its clients for a long time will provide a good understanding of the characteristics of the company, resulting in a level of time efficiency in the financial statement audit process, which then has a positive effect on the timeliness of the publication of the Financial Statements.